2013
DOI: 10.1002/sia.5229
|View full text |Cite
|
Sign up to set email alerts
|

XPS analysis of chitosan–hydroxyapatite biomaterials: from elements to compounds

Abstract: Chitosan (Cs) and hydroxyapatite (Ha) were analysed by X-ray photoelectron spectroscopy (XPS). Phosphorylated Cs microparticles and hybrid Cs/Ha microparticles were prepared and analysed by XPS before and after immersion in a solution 1.5 times more concentrated than a simulated body fluid (SBF). The accuracy of spectrum recording, peak decomposition and peak component assignment was insured by a post-control of charge stabilization, and by the examination of correlations between spectral data guided by stoich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 44 publications
20
55
0
1
Order By: Relevance
“…Spectral analysis was performed using the XPS Peak software v 4.1. The major N 1s contribution near 399.4 eV was due to non-protonated amine or amide (Nnp); and the higher binding energy side at 401.4 eV could be assigned to protonated amine groups (Npr) [31,32]. 12 The bead grinding method described in our previous study was adopted here with a minor modification [33].…”
Section: Characterization Of Chitosan Distribution In Ac Microcapsulesmentioning
confidence: 99%
“…Spectral analysis was performed using the XPS Peak software v 4.1. The major N 1s contribution near 399.4 eV was due to non-protonated amine or amide (Nnp); and the higher binding energy side at 401.4 eV could be assigned to protonated amine groups (Npr) [31,32]. 12 The bead grinding method described in our previous study was adopted here with a minor modification [33].…”
Section: Characterization Of Chitosan Distribution In Ac Microcapsulesmentioning
confidence: 99%
“…Three kinds of peaks can be noticed in pure HA spectrum which were attributed to the adventitious organic contaminants or the adsorption of impurity hydrocarbons during the synthesis procedure. These peaks do not affect the interpretation of our results after CS addition [19,24]. The peak located at 284.6 eV was assigned to the C-C and C-H appeared in all samples and remained almost constant in their areas [24].…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 63%
“…These peaks do not affect the interpretation of our results after CS addition [19,24]. The peak located at 284.6 eV was assigned to the C-C and C-H appeared in all samples and remained almost constant in their areas [24]. However, in all nanocomposite samples, new peak was observed in the range of 286.3 to 288 eV which was related to the chemical bond between carbon and nitrogen or oxygen [C-(N,O)].…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 75%
See 1 more Smart Citation
“…For CL6, There was an N1s peak near 400.0 eV due to the existence of non‐protonated amine or amide (Nnp). And there was a new peak near 285.4 eV which was attributed to CN in the spectrum of CL6, besides those peaks of CO, CO, and CH . The peaks of N1s and CN indicated that NCTS had been successfully blended with PLA in the electrospun nanofibrous mat.…”
Section: Resultsmentioning
confidence: 96%